PERANAN INDIKATOR-INDIKATOR KETERAMPILAN KOMUNIKASI TERAPEUTIK DALAM MEMPREDIKSI KEPUASAN KERJA PERAWAT RSJ NEGERI DI MAKASSAR - Mutiarini Mubyl; Fitriani Latief (P3M STIEM BONGAYA, 2019)
Job satisfaction is an important element in the clinical-industrial work. To measure job satisfaction can be seen from various factors that influence it. This study measures nurses' job satisfaction in psychological terms, namely therapeutic communication skills. The purpose of this study was to determine the role of therapeutic communication skill indicators in predicting job satisfaction in nurses of state mental hospitals in Makassar. The method used is quantitative non-experimental (ex post facto), multiple regression test. The results showed that the therapeutic communication skills indicator played a role in predicting job satisfaction by 31.7% (p <0.01) with the most instrumental indicator being the empathy indicator of 1,604 (t-count> t-table: 4,459> 2,626; sig. 000). The conclusion was that nurses who used empathetic therapeutic communication skills (empathy) were more predictable in job satisfaction compared to other communication skills such as; presence (attending skills), respect skills, and responsiveness.